2018
DOI: 10.1093/ijnp/pyy046
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Exposure Reduces Parvalbumin Expression in the Rat Hippocampus through an Imbalance of Redox Mechanisms: Restorative Effect of the Antipsychotic Lurasidone

Abstract: BackgroundPsychiatric disorders are associated with altered function of inhibitory neurotransmission within the limbic system, which may be due to the vulnerability of selective neuronal subtypes to challenging environmental conditions, such as stress. In this context, parvalbumin-positive GABAergic interneurons, which are critically involved in processing complex cognitive tasks, are particularly vulnerable to stress exposure, an effect that may be the consequence of dysregulated redox mechanisms.MethodsAdult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 50 publications
3
35
0
1
Order By: Relevance
“…Moreover, GABAergic interneurons that express parvalbumin (PV) and somatostatin (SST), are extremely vulnerable to the detrimental consequences of stress exposure [ 36 , 37 ]. Indeed, several studies reported that chronic stress decreases Pv and Sst mRNA levels, as well as the number of neurons expressing these markers [ 32 , 36 , 37 , 38 ].…”
Section: Molecular Mechanisms Of the Stress Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, GABAergic interneurons that express parvalbumin (PV) and somatostatin (SST), are extremely vulnerable to the detrimental consequences of stress exposure [ 36 , 37 ]. Indeed, several studies reported that chronic stress decreases Pv and Sst mRNA levels, as well as the number of neurons expressing these markers [ 32 , 36 , 37 , 38 ].…”
Section: Molecular Mechanisms Of the Stress Responsementioning
confidence: 99%
“…For instance, we have shown that CMS exposure reduces the expression of neuroplastic proteins [ 114 ] and alters synaptic mechanisms involved in the glutamatergic function and local protein synthesis [ 111 ]. Moreover, exposure to CMS is associated with alterations in the glucocorticoid signaling [ 113 ], enhanced expression of inflammatory markers as well as an imbalance of redox mechanisms [ 38 , 110 ], all of which have been associated with schizophrenia.…”
Section: Stress Exposure and Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, the increased levels of peripheral and central inflammatory markers observed in a large subset of MDD subjects (Raison et al, 2006; Howren et al, 2009; Dowlati et al, 2010), the high co-morbidity between MDD and various non-psychiatric illnesses associated with inflammatory conditions (Anisman, 2008; Berge and Riise, 2015; Réus et al, 2017), and the development of MDD in a high percentage of patients under interferon regimen (Raison et al, 2009; Udina et al, 2012) clearly support the relevance of a neuroinflammatory component in MDD. In addition, while changes in immune/inflammatory response have been found in MDD experimental models based on both the genetic and the environmental components of the disease (Chourbaji et al, 2011; Couch et al, 2013; Macchi et al, 2013; Rossetti et al, 2016; Wang et al, 2018), several studies indicate the immune/inflammatory system as a potential target for the pharmacological treatment of MDD (Molteni et al, 2013; Kv et al, 2018; Rossetti et al, 2018a,b; Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%